The Endocannabinoid System Affects Myocardial Glucose Metabolism in the DOCA-Salt Model of Hypertension - Agnieszka Polak; Ewa Harasim-Symbor; Barbara Malinowska; Irena Kasacka; Alicja Lewandowska; Adrian Chabowski (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Recent interest in the use of cannabinoids as therapeutic agents has revealed the involvement of the endogenous cannabinoid system (ECS) in the regulation of the cardiovascular system in hypertension. Abnormalities in glucose metabolism and insulin action are commonly detected in hypertensive animals. Thus, potential antihypertensive drugs should be investigated with respect to modulation of glucose homeostasis. Therefore, the aim of the present study was to evaluate the effects of the ECS activation after chronic fatty acid amide hydrolase inhibitor (URB597) administration on plasma glucose and insulin concentrations as well as parameters of myocardial glucose metabolism in the deoxycorticosterone acetate (DOCA)-salt hypertensive rats, an animal model of secondary hypertension. Methods: Hypertension was induced by DOCA (25mg/kg) injections and addition of 1% NaCl in the drinking water for six weeks. Chronic activation of the ECS was performed by URB597 (1mg/kg) injections for two weeks. We examined fasting plasma levels of insulin (ELISA), glucose and intramyocardial glycogen (colorimetric method). Expressions of glucose transporters (GLUT1, 4) and selected proteins engaged in GLUT translocation as well as glucose metabolism were determined using Western blotting. Results: Hypertension induced hypoinsulinemia with concomitant lack of significant changes in glycemia, reduced intramyocardial glycogen content and increased pyruvate dehydrogenase (PDH) expression in the cardiac muscle. Importantly, chronic URB597 administration in the hypertensive rats increased insulin concentration, elevated plasmalemmal GLUT1 and GLUT4 expression and concomitantly improved myocardial glycogen storage. Conclusion: Chronic administration of fatty acid amide hydrolase (FAAH) inhibitor has potential protective properties on myocardial glucose metabolism in hypertension.